1987
DOI: 10.1007/bf03259869
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Reactions to Thrombolytic Agents

Abstract: The use of thrombolytic agents to dissolve coronary artery thrombi causing acute transmural myocardial infarctions has been shown to decrease short term mortality, and improve left ventricular function, in patients with acute transmural myocardial infarction. Several thrombolytic agents are currently available which differ mainly in cost, antigenicity, and mechanism of action. Current investigations are being directed at finding safer, more effective thrombolytic agents and at developing optimal therapy follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…The elderly population is more likely to experience streptokinase adverse effects, particularly bleeding and hypotension [16,17]. Similarly, in our study, we found the incidence of adverse effects to be higher in Group C (mean age: 66 ± 2 years) compared with Group A (mean age: 39 ± 3 years).…”
Section: Discussionsupporting
confidence: 81%
“…The elderly population is more likely to experience streptokinase adverse effects, particularly bleeding and hypotension [16,17]. Similarly, in our study, we found the incidence of adverse effects to be higher in Group C (mean age: 66 ± 2 years) compared with Group A (mean age: 39 ± 3 years).…”
Section: Discussionsupporting
confidence: 81%
“…There are several thrombolytic agents that differ in cost, antigenicity and currently more investigations are being directed to find safer and more effective thrombolytic agents. Nevertheless, the thrombolytic agents are associated with hypotension, arrhythmias and hemorrhagic complications,[20] which might be a risk of intracranial bleeding and many more systemic or major bleeding risks and death. It was interesting to find the knowledge of paramedics regarding the risks of thrombolysis therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although they can be effective, thrombolytics may greatly effect hemostasis, resulting in some significant side effects. 62 Instead of treating blood clots, drugs such as captopril and ramipril can reduce the load on blood vessels. 63 These belong to the class of angiotensin-converting enzyme inhibitors that work by decreasing angiotensin II levels.…”
Section: Current Clinical Managementmentioning
confidence: 99%